2020
DOI: 10.1111/zph.12751
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of domestic swine to influenza A viruses in Ghana suggests unidirectional, reverse zoonotic transmission at the human–animal interface

Abstract: Influenza A viruses (IAVs) have both zoonotic and anthroponotic potential and are of public and veterinary importance. Swine are intermediate hosts and ‘mixing vessels’ for generating reassortants, progenies of which may harbour pandemic propensity. Swine handlers are at the highest risk of becoming infected with IAVs from swine but there is little information on the ecology of IAVs at the human–animal interface in Africa. We analysed and characterized nasal and throat swabs from swine and farmers respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…A total of 82% (58/71) of included studies sequenced and/or analyzed partial genomes, especially the HA and/or NA and/or MP. A total of 16% (11/71) studies sequenced and/or analyzed whole genomes [ 26 , 44 , 47 , 54 , 55 , 57 , 63 , 73 , 75 , 95 , 98 ]. One study sequenced whole genomes but analyzed only the HA genes [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 82% (58/71) of included studies sequenced and/or analyzed partial genomes, especially the HA and/or NA and/or MP. A total of 16% (11/71) studies sequenced and/or analyzed whole genomes [ 26 , 44 , 47 , 54 , 55 , 57 , 63 , 73 , 75 , 95 , 98 ]. One study sequenced whole genomes but analyzed only the HA genes [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis of the MP genes showed clustering of a human (A/Ghana/KM001/2015(H1N1)) and swine H1N1pdm09 strains (A/swine/Nigeria/IBDVR004/2015(H1N1) and A/swine/Nigeria/IBDVR005/2015) (bootstrap = 68%) [ 42 ]. The following season (2016–2017), H1N1pdm09 strains were detected in 1.4% (17/1200) of Ghanaian swine [ 44 ]. All swine H1N1pdm09 strains sampled in Nigeria, Ghana, Cameroon, Kenya, Togo, and Egypt between 2014 and 2017 evolved from the human A/California/04/2009(H1N1) vaccine strain and clustered according to the year of sampling in the H1 and MP phylogenies [ 42 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is in stark contrast to Asia, where strains of both origins and reassortants between them co-circulate [10]. Little is known about the status of pigs in Africa [146].…”
Section: Swinementioning
confidence: 93%
“…However, a study performed by Wong et al [ 107 ] showed that the combination of these two measures is an effective strategy to prevent disease [ 107 ]. Ayim-Akonor et al suggested that poor biosafety management may enable easier cross-species transmission of influenza virus between humans and pigs [ 108 ].…”
Section: Influenzamentioning
confidence: 99%